The role of entrepreneurial self-efficacy and resilience in influencing entrepreneurial transition decisions from hybrid to full-time entrepreneurship - Myres, Kerrin (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.